Determining the Probability of Cyberattacks (European Journal of Formal Sciences and Engineering, 2021)
The use of information is inextricably linked with its security. The presence of vulnerabilities enables a third party to breach the security of information. Threat modeling helps to identify those infrastructures, which would be most likely exposed to cyberattacks. In some cases, however, threat modeling can not be classified as sufficient method of protection. This paper entitled “Determining the probability of cyberattacks” presents an analysis of different techniques with an attempt to identify the most informative parameters and cyberattack prediction markers, which would lay the foundation for the development of cyberattack probability functions. Next, it would be relevant to design such cyberattack probability functions, which would be used upon the initial identification of a cyberattack. The findings of this research could be applied during the future assessment of risk levels of information systems to ensure more effective information security management.
Keywords: Probability of cyberattacks, information security, cyber security, risk management, risk prediction.